Pre-Service Teachers’ Beliefs on the Subject-Specific Use of Digital Media in Biology Classrooms - Funke, Maja; Bergmann-Gering, Alexander; Müller, Kai; Zabel, Jörg (Technology, knowledge and learning, 2025)
Pre-service teacher (PST) training in Germany largely fails to prepare prospective teachers adequately for the subject-specific use of digital media. In order to promote their digital competences as well as their intention to use digital media, teacher training needs to adapt. Utilizing Theory of Planned Behavior (TPB), this study aims to identify beliefs on the subject-specific use of different digital media in biology classroom. Within a weekly course on different scientific inquiry methods, pre-service biology teachers used various digital media and wrote reflections on advantages and disadvantages of the digital media they used. Through analysis of these written reflections ( n = 85) it was possible, to differentiate the TPB constructs into 38 subcategories. Across all media, we were able to identify most beliefs in the area of behavioral and control beliefs, while normative beliefs and self-efficacy expectations were rarely expressed. At the level of the inductive categories, however, the beliefs were often expressed with different frequencies depending on the medium used. The results allow a more subject-specific differentiation of TPB’s constructs for digital media use in order to design a measuring instrument to evaluate biology teacher training courses. In addition, the results indicate that PSTs’ intention to use digital media in the biology classroom also differs depending on the medium used. These findings provide actionable insights for the design of teacher training programs that specifically target beliefs, i.e. by confronting PSTs with a variety of different digital tools, to enhance the effective use of digital media in biology classrooms.